The Relationship of Special Education Teacher Performance on Observation Instruments With Student Outcomes. (January 2021) - Johnson, Evelyn S.; Zheng, Yuzhu; Crawford, Angela R.; Moylan, Laura A.
In this study, we examined the relationship of special education teachers' performance on the Recognizing Effective Special Education Teachers (RESET) Explicit Instruction observation protocol with student growth on academic measures. Special education teachers provided video-recorded observations of three instructional lessons along with data from standardized, curriculum-based academic measures at the beginning, middle, and end of the school year for the students in the instructional group. Teachers' lessons were evaluated by external, trained raters. Data were analyzed using many-faceted Rasch measurement (MFRM), correlation, and multiple regression. Teacher performance on the overall protocol did not account for statistically significant variance in student growth beyond that of students' beginning of the year academic performance. Teacher performance on an abbreviated protocol comprised of items that had average or higher item difficulties on the MFRM analysis accounted for an additional 4.5% of variance beyond that of beginning of the year student performance. Implications for further research are discussed.